Answer:
See below for answers (in bold) and explanations
Step-by-step explanation:
Part A: (h+t)(x) = h(x) + t(x) = (2x-5) + (6x+4) = 2x - 5 + 6x + 4 = 8x - 1
Part B: (h*t)(x) = h(x) * t(x) = (2x-5) * (6x+4) = (2x)(6x) + (2x)(4) + (-5)(6x) + (-5)(4) = 12x² + 8x - 30x - 20 = 12x² - 22x - 20
Part C: h(t(x)) = h(6x + 4) = 2(6x + 4) - 5 = 12x + 8 - 5 = 12x + 3
A. for the circumference it is C=pi(d)=pi(2r)=pi(10)= 31.4 ft
b. for the area it is A=pi(r)^2=pi(5)^2=pi(25)= 78.5 ft squared
c. since the are is 78.5 ft squared multiply by $4.50= $353.25 to floor the circle.
Answer:
ok
Step-by-step explanation:
Answer:
The identity property
Step-by-step explanation:
.......
Answer:
x=1/3
Step-by-step explanation:
9x+5-3=5
9x=3
x=1/3